Anesthetic conduction in giant ovarian tumor - José Luis Muñoz Gallardo; Arletys Curbelo Hernández; José Luis Muñoz Fernández (Correo Científico Médico)
Introduction: Teratoma is a germ cell tumor that frequently occurs in childbearing age, and is mostly benign.